Energy Recovery from Cannabis Residues by Combustion with and Without Steam Explosion Pretreatment in Different Air Coefficients - Rafael Eloy de Souza; Eduardo Lins de Barros Neto; Jean-Michel Lavoie; Bruna Rego de Vasconcelos (Clean Technologies)
Alternative options have been studied to mitigate the negative impact of fossil fuel sources, mainly especially when it comes to alternative energy sources. In this work, cannabis residues have been considered as a potential biomass residues for energy recovery due to their energy content, and the increase in the cannabis market in Canada has created an opportunity niche for treating and valorizing these residues as energy. This study thus aims to investigate the potential of energy recovery from cannabis residue pellets via combustion and the impact of steam explosion on the pellets’ properties as well as combustion behavior. Two batches of pellets were produced namely with and without the steam explosion pretreatment. The properties of the pellets were then compared to those of the CANplus certification. Cannabis pellets were then combusted at 290 °C in a fixed-bed reactor using three different air coefficients (α) ranging from 1 to 1.3 (α = 1.0, α = 1.15, and α = 1.3). Flue gas quantification was performed using gas chromatography combined with a NOx detector. Results showed that the properties of this biomass is comparable to other sources of lignocellulosic biofuels. The steam explosion pretreatment enhanced pellet properties, including higher heating value (HHV), ash content, durability, and fines allowing the product to reach the CANplus requirements. The air coefficients influenced the emission levels, with an optimal value at α = 1.15, that indicated an improved combustion quality. However, steam explosion negatively affected combustion efficiency, resulting in incomplete combustion. Overall, cannabis residues show a strong potential for energy recovery and could offer a sustainable option for bioenergy applications.